2018
DOI: 10.1002/jcsm.12318
|View full text |Cite
|
Sign up to set email alerts
|

Building strength, endurance, and mobility using an astaxanthin formulation with functional training in elderly

Abstract: BackgroundBuilding both strength and endurance has been a challenge in exercise training in the elderly, but dietary supplements hold promise as agents for improving muscle adaptation. Here, we test a formulation of natural products (AX: astaxanthin, 12 mg and tocotrienol, 10 mg and zinc, 6 mg) with both anti‐inflammatory and antioxidant properties in combination with exercise. We conducted a randomized, double‐blind, placebo‐controlled study of elderly subjects (65–82 years) on a daily oral dose with interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…ASX has been widely studied in vivo models for its potential role in preventing muscle loss and ameliorate muscle strength and exercise performance, and there is preliminary evidence in endurance performance and post-exercise recovery in humans [ 49 ]. In healthy older adults, in particular, a recent study has shown how supplementation with ASX has improved muscle strength and muscle size of cross-sectional area (CSA), in addition to the increase in endurance and distance covered with physical training alone [ 50 ]. Therefore, ASX supplementation, in combination with a functional training program, can potentially improve muscle strength, endurance, and mobility in the elderly.…”
Section: Astaxanthin: From a Diet Component To An Anti-aging Supplmentioning
confidence: 99%
“…ASX has been widely studied in vivo models for its potential role in preventing muscle loss and ameliorate muscle strength and exercise performance, and there is preliminary evidence in endurance performance and post-exercise recovery in humans [ 49 ]. In healthy older adults, in particular, a recent study has shown how supplementation with ASX has improved muscle strength and muscle size of cross-sectional area (CSA), in addition to the increase in endurance and distance covered with physical training alone [ 50 ]. Therefore, ASX supplementation, in combination with a functional training program, can potentially improve muscle strength, endurance, and mobility in the elderly.…”
Section: Astaxanthin: From a Diet Component To An Anti-aging Supplmentioning
confidence: 99%
“…The CK and aspartate aminotransferase (AST) activities in serum were significantly increased with soccer training without treatment but were lowered with astaxanthin administration (45). In a randomized, double-blind, placebo-controlled study, Liu et al (46) examined a test formulation consisting of astaxanthin (12 mg), tocotrienol (10 mg) and zinc (6 mg) on building strength, endurance and mobility in exercise training among the elderly. A total of 42 elderly subjects (aged 65-85 years) were recruited, fed with test formulation or placebo for 4 months and trained with increasing intervals of incline walking for three months (three times weekly for 40-60 min).…”
Section: Effects Of Astaxanthin On Skeletal Muscle: Evidence From Hummentioning
confidence: 99%
“…identified a greater endurance in a 6-min walk upon exercise training in both experimental groups. The subjects administered astaxanthin formulation had higher MVC and CSA, indicating improved muscle strength and size as compared to the placebo-treated exercised subjects (46). A recent study by Takami et al (47) assessed whether foods containing antioxidants (such as catechin, astaxanthin, quercetin, glutathione and anthocyanin) could boost aerobic metabolism during exercise training.…”
Section: Effects Of Astaxanthin On Skeletal Muscle: Evidence From Hummentioning
confidence: 99%
See 1 more Smart Citation
“…Astaxanthin could improve the muscle strength of elderly. And it has been shown that the right amount of astaxanthin combined with functional training can significantly improve the muscle strength, endurance and flexibility of the elderly (Liu et al, 2018). The edible history of astaxanthin has been in existence for more than 20 years and there has been no safety problems.…”
Section: Astaxanthin Application 41 Health Productmentioning
confidence: 99%